2011
DOI: 10.1345/aph.1q283
|View full text |Cite
|
Sign up to set email alerts
|

Ferumoxytol Infusion in Pediatric Patients with Gastrointestinal Disorders: First Case Series

Abstract: Ferumoxytol doses of up to 12 mg elemental iron/kg administered over 15-60 minutes seem to be well tolerated in pediatric patients. Larger prospective studies are needed to determine the incidence and severity of adverse effects associated with ferumoxytol, both during administration and immediately after. Long-term studies will be required to assess to risk for iron overload toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 7 publications
3
8
0
Order By: Relevance
“…We did not observe any hypersensitivity reaction in the 49 pediatric patients. This is in accordance with previous case reports, stating lack of allergic reactions in a study of six pediatric patients (20). Hypersensitivity reactions were reported in 0.2% of adult CKD patients who received ferumoxytol for anemia treatment (1).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…We did not observe any hypersensitivity reaction in the 49 pediatric patients. This is in accordance with previous case reports, stating lack of allergic reactions in a study of six pediatric patients (20). Hypersensitivity reactions were reported in 0.2% of adult CKD patients who received ferumoxytol for anemia treatment (1).…”
Section: Discussionsupporting
confidence: 94%
“…Hassen and colleagues reported that ferumoxytol was overall well tolerated in six pediatric patients with gastrointestinal disorders except for one case of mild pruritus (20). Klenk and colleagues found no objective or subjective adverse events in 22 patients (3) and neither did Thompson and colleagues in seven patients (4).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the associated stigma persists and is often linked to all IV iron formulations, including the much safer and highly effective newer formulations . The three primary formulations that have been used historically in pediatrics are iron sucrose (IS), low molecular weight iron dextran (LMWID), and sodium ferric gluconate complex (FG), though newer formulations such as ferric carboxymaltose and ferumoxytol are now being studied as well . A few studies in small pediatric cohorts, mostly in hematology patients with IDA, have demonstrated that IV iron is both safe and effective .…”
Section: Introductionmentioning
confidence: 99%
“…Iron oxide nanoparticles are not approved for clinical use in children and applications in the US are done through an investigational new drug (IND) application with the FDA. Safety data in paediatric patients are limited, but have not shown clinically significant side effects so far [52, 53]. The recently renewed safety discussion around iron products does not relate to new toxic effects [24], but has to be taken seriously and has led to a black box warning by the FDA.…”
Section: Discussionmentioning
confidence: 99%